Distinct Nitrogen Provisioning From Organic Amendments in Soil as Influenced by Farming System and Water Regime - Lori, Martina; Symanczik, Sarah; Mäder, Paul; Efosa, Norah; Jaenicke, Sebastian; Buegger, Franz; Tresch, Simon; Goesmann, Alexander; Gattinger, Andreas (Frontiers in Environmental Science, 2018)
The majority of soil organic nitrogen (N) is bound in protein-like compounds and therefore its proteolysis in peptides and amino acids is considered the initial and rate limiting step of N mineralization. Proteolysis of N bound in organic fertilizer and subsequent provisioning for crops is a central element in agro-ecological intensification. Long-term farming system effects on N provisioning from organic fertilizer to crops and its underlying functional microbial communities were analyzed in experiments conducted in soils from the “DOK” system comparison trial (bio-Dynamic, bio-Organic, and “Konventionell”) DOK farming system comparison subjected to optimal and future projected drought scenarios. A plant nutrition experiment using 15N labelled lupine as a fertilizer (green manure) identified 30% higher amounts of N derived from fertilizer in ryegrass grown on organically compared to conventionally managed soil, but only when subjected to dry conditions. A second experiment, also amended with lupine green manure, assessed the effect of farming system and drought stress on N cycling microbes with a focus on alkaline (apr) and neutral (npr) metallopeptidase encoding microbial communities. apr encoding microbial communities were more strongly affected by farming system and water treatment than npr encoding communities. Differences in structure and diversity of apr encoding microbial communities showed concomitant patterns with distinct N provisioning from organic fertilizer in the plant nutrition experiment. It is suggested that conventionally managed systems are less capable in maintaining diversity and initial structure of apr encoding microbial communities when subjected to drought scenarios. Overall, we demonstrated organically managed soils to provide a more stable N provisioning potential from organic fertilizer under future drought scenarios, likely facilitated by a distinct and more adaptive proteolytic microbial community. This work contributes to an in-depth comprehension of yet poorly studied fundamental soil processes and helps developing strategies to maintain a versatile and functioning microbial community in a rapidly changing environment.